Analysis of Trace Heavy Metal in Solution Using Liquid Cathode Glow Discharge Spectroscopy - Duixiong Sun; Xinrong Ma; Jiawei Chang; Guoding Zhang; Maogen Su; Marek Sikorski; Vincent Detalle; Xueshi Bai (Sensors)
Heavy metal pollution, particularly from cadmium (Cd) and copper (Cu), poses significant environmental and health risks. To address the need for efficient, portable, and sensitive detection methods, this study introduces an improved atmospheric pressure glow discharge atomic emission spectrometry (APGD-AES) technique for quantifying Cd and Cu in water samples. The APGD-AES method offers key advantages, including low energy consumption (<33 W), high excitation energy, and compact design. The system was optimized for a discharge voltage of 550 V (Cd) and 570 V (Cu), a flow rate of 3.6 mL/min, and a solution pH of 1.0. Under these conditions, detection limits reached 16 µg/L for Cd and 1.3 µg/L for Cu. APGD-AES was tested on real water samples, including sewage and tap water, demonstrating compliance with national safety standards and comparable performance to graphite furnace atomic absorption spectrometry (GFAAS). This technique shows promise for real-time, on-site monitoring of trace heavy metals due to its portability, precision, and cost-efficiency.